Religious education and social justice: reflections on an approach to teaching religious education - Hannam, Patricia (Journal of Religious Education, 2022)
This paper examines the possible relationship between religious education and social justice. A consideration of what it is that education in the public sphere should seek to achieve, in a normative sense, is followed by an explanation of how we conceptualise social justice in this paper. This leads us to be able to explain why the relationship between teacher and child or young person is significant and why it is insufficient to conceptualise religious education only in terms of knowledge. Instead, we propose that the teacher’s first responsibility when beginning any course of study is to bring the child to attend to their experience and that of their wider community. We argue that curriculum cannot be made in isolation of the context of the child and that education is not something that takes place in abstraction. Rather, it requires the teacher to be attentive to this particular child, the one who is here now, and in this particular place. Having begun to set out the educational position of our argument, we show how this is working practically guided by a Locally Agreed Syllabus for Religious Education: Living Difference IV, in religious education taught in a school in an area of high deprivation in the southeast of Hampshire. UK.